2019
DOI: 10.1101/702183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Warm nights disrupt global transcriptional rhythms in field-grown rice panicles

Abstract: 33In rice, a small increase in nighttime temperatures reduces grain yield and quality. How warm nighttime 34 temperatures (WNT) produce these detrimental effects is not well understood, especially in field conditions 35 where the normal day to night temperature fluctuation exceeds the mild increase in nighttime temperature. 36We observed genome-wide disruption of gene expression timing during the reproductive phase on field-37 grown rice panicles acclimated to 2-3°C WNT. Rhythmically expressed transcripts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Moreover, rice flowers have a noted sensitivity to high nighttime temperatures (Desai et al, 2019). Selecting appropriate sampling times will have to consider these various aspects of stress response.…”
Section: Stress Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, rice flowers have a noted sensitivity to high nighttime temperatures (Desai et al, 2019). Selecting appropriate sampling times will have to consider these various aspects of stress response.…”
Section: Stress Selectionmentioning
confidence: 99%
“…For developing rice flowers, extensive physiological, agronomic, and anatomical examinations of heat stress responses have identified sensitive developmental stages and tissues (Cheabu, Moung‐Ngam, Arikit, Vanavichit, & Malumpong, 2018 ; Jagadish, Craufurd, & Wheeler, 2007 ). Moreover, rice flowers have a noted sensitivity to high nighttime temperatures (Desai et al, 2019 ). Selecting appropriate sampling times will have to consider these various aspects of stress response.…”
Section: Enhancing High Temperature Resilience By Targeting Scgrnsmentioning
confidence: 99%
“…However, until now, no study has been reported on QTLs mapping for GL and GW under HNT stress in bi-parental populations in rice worldwide. Despite the increasing knowledge of QTL mapping, metabolomics 65 , and transcriptomic 66 , 67 responses to HNT stress in rice, the understanding and dissection of genetic basis of grain quality traits and HNT stress tolerance in rice is still limited. Hence, based on our best knowledge and recent survey of the literature & databases, in the United States, this is the first study to identify genetic loci and putative candidate genes controlling grain quality traits and HNT stress tolerance mechanisms in tropical japonica (TRJ) rice under HNT stress.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 1°C increase in the temperature during the night can decrease rice grain yield by 10% (Peng et al, 2004). Furthermore, warm night temperatures disrupt rhythmically expressed genes, particularly those genes driven by thermocyles (Desai et al, 2019), which has impacts upon productivity.…”
Section: Introductionmentioning
confidence: 99%